Exercise induced pulmonary vasoconstriction. - Kulik, T J (1983)
Pulmonary vascular resistance normally falls or remains unchanged during exercise. Seven children with pulmonary hypertension were exercised during cardiac catheterisation after operative correction of ventricular septal defect (6) and truncus arteriosus (1). Except for the presence of moderate pulmonary hypertension, resting haemodynamics in these seven children were similar to those of normal children of equal age, but during exercise the postoperative patients showed a rise rather than a fall (+2% vs -18%) in total pulmonary vascular resistance. Two of the seven children had a substantial increase in pulmonary arteriolar resistance during exercise (from 509 to 715 dyne s cm-5 in one patient and from 606 to 828 dyne s cm-5 in the other). These two patients did not differ from normal children in respect of arterial or mixed venous oxygen saturations or of pH with exercise, nor was left atrial pressure related to the rise in pulmonary resistance. These two patients, however, had only a small rise in cardiac output during exercise (6.8% and 43.1%) in spite of a substantial increase in oxygen consumption (121% and 373%). One of the patients with exercise-induced pulmonary vasoconstriction had an 82% increase in resting pulmonary vascular resistance over a five year period subsequent to her first exercise study. Analysis of these data, and those previously reported, suggests that exercise induced pulmonary vasoconstriction may occur in 10 to 25% of patients who survive correction of certain congenital cardiac defects. The vasoconstriction cannot be attributed to abnormal changes in blood gases or left atrial pressure, and may be an early sign of progressive pulmonary hypertension.